Insurgency, Counterinsurgency and Human Security: A Case Study of Armed Violence in Papua during the COVID-19 Pandemic - Stefani Selina Prameswari; Nadia Amani Husna (Jurnal Hubungan Internasional)
Secretary-General of the United Nations, António Guterres, asserted that during the COVID-19 pandemic, a global ceasefire must be carried out to bridge human rescue assistance, assist diplomacy, and facilitate the spread reduction of the virus among vulnerable populations, especially in conflict regions. However, a pandemic can trigger resistance due to declining economic conditions, leaving opportunities for opposition movements to open. This paper endeavors to discern the dynamics of insurgency and counterinsurgency during the COVID-19 pandemic, especially in Papua, with situations of armed violence between TNI-Polri and West Papua National Liberation Army (TPNPB). The authors argue that the vulnerability of the Papuan people during the COVID-19 pandemic, which is spread across almost all sectors, the dynamics of insurgency and counterinsurgency endanger human security and increase the suffering of Papuan people, especially those who live in conflict areas such as Intan Jaya, Mimika, Puncak, and Nduga. Therefore, using qualitative methods and secondary analysis, the authors discuss insurgency, counterinsurgency, threats, and human security in Papua during the COVID-19 pandemic.